Bacterium-Mediated RNA Interference: Potential Application in Plant Protection - Goodfellow, Simon (Plants (Basel), 2019)
RNAi has emerged as a promising tool for targeting agricultural pests and pathogens and could provide an environmentally friendly alternative to traditional means of control. However, the deployment of this technology is still limited by a lack of suitable exogenous- or externally applied delivery mechanisms. Numerous means of overcoming this limitation are being explored. One such method, bacterium-mediated RNA interference, or bmRNAi, has been explored in other systems and shows great potential for application to agriculture. Here, we review the current state of bmRNAi, examine the technical limitations and possible improvements, and discuss its potential applications in crop protection.